The Influence of Islamic Branding, Halal Awareness, and Product Ingredients on Purchasing Decisions of Cosmetic and Skincare Products - Ary Dean Amri; Putti Sherna; Anisa Putri Marpaung; Alda Mariatul Kiptiah; Fitriani .; Benny Zulfikar; Naufal Alfarizie HSB; Raden Aqsal Safatullah (JOURNAL OF SHARIA ECONOMICS, 2023)
P This study aims to identify the influence of Islamic branding, halal awareness, and product ingredients on the intention to buy cosmetic and skincare products among Muslim women of generation Z in Jambi Province. The use of cosmetic and skincare products that comply with Islamic principles is increasingly important for Muslim women who want to ensure that the products they use are halal and in accordance with their religious beliefs. Therefore, factors such as Islamic branding, halal awareness, and product ingredients are important considerations in their purchasing decisions. This study used a survey method by distributing questionnaires to a sample of generation Z Muslim women in Jambi Province. The data collected was analyzed using multiple linear regression methods to examine the relationship between Islamic branding, halal awareness, and product ingredients on buying interest in cosmetic and skincare products. In addition, factor analysis was also carried out to identify the factors that most influence purchasing decisions.This research makes an important contribution in understanding the factors that influence purchasing decisions for cosmetic and skincare products among Muslim women of generation Z. The results of this research can be a reference for cosmetic and skincare companies in developing more effective marketing strategies that take into account religious values and the needs of Muslim consumers. In addition, this research can also be a basis for further research in a broader context.